OC-072 Use Of A Novel Self-expanding Metal Stent To Allow For Endoscopic Drainage And Necrosectomy Of Pancreatic Fluid Collections. (9th June 2014) - Huggett, MT; Oppong, KW; Pereira, SP; Mitra, V; Charnley, RM; Nayar, MK
Abstract : Introduction: Post-inflammatory peri-pancreatic fluid collections are frequent sequelae of severe acute pancreatitis. Collections are at risk of suppurative infection complicated by pancreatic necrosis. Over the last decade there has been an increasing emphasis on minimally invasive drainage procedures, including EUS-guided cyst-gastrostomy, and these approaches seem to be associated with lower morbidity and mortality. Access to the necrosis cavity has however been severely limited by having to maintain the tract with small diameter plastic stents. Recently, a novel flanged fully covered self-expanding metal stent (FCSEMS; NAGI stent, Taewoong Medical, Korea) has been developed to allow for better drainage of infected necrosis and easier endoscopic access into the cavity. Setting: A non-randomised prospective multicentre phase II study to determine the safety and efficacy of FCSEMS endoscopic cyst-gastrostomy in the management of complex/infected pancreatic fluid collections. Methods: Patients were included if they had evidence of a pancreatic fluid collection which was deemed to be amenable for EUS-guided drainage after discussion at a HPB multidisciplinary meeting. Patients selected for EUS-guided drainage had cross sectional imaging (MR or CT) performed within 2 weeks of the procedure and then an EUS assessment was made of the necrotic component. The collection was punctured using a cystotome and the FCSEMS inserted over a guidewire with fluoroscopic control. Repeat procedures were performed as necessary. Results: A total of 11 patients (8 male, 3 female) were included in the study. Median age was 57.3 years. The aetiology of the collection was gallstones in 6 patients, idiopathic in 3, ischaemic in 1 and drug-induced in 1. Ten patients had evidence of at least 30% necrosis within the collection. Mean diameter of the collection was 15 cm and EUS-guided puncture was initially performed in all patients. The tract was dilated with a balloon in 6 patients. Stent insertion was either with a 20 mm (7 patients) or 30 mm (4 patients) length FCSEMS. Ten patients underwent endoscopic necrosectomy, with a median of 3 procedures (range 1–10). Significant reduction in the size of collection was achieved in all patients. Adverse events included stent migration in 3 (2 spontaneously and 1 during necrosectomy). Two patients died of complications of severe acute pancreatitis. Conclusion: FCSEMS insertion is feasible and safe for drainage of pancreatic fluid collections. It allows repeated through the stent necrosectomy procedures and appears to be a major advance in the management of infected pancreatic necrosis. Disclosure of Interest: None Declared.